Programmable Analog Circuits with Neuromorphic Nanostructured Platinum Films - Stefano Radice; Filippo Profumo; Francesca Borghi; Andrea Falqui; Paolo Milani (Advanced Electronic Materials)
Abstract Self‐assembled nanoparticle or nanowire networks have recently come under the spotlight as systems able to emulate brain‐like data processing performances by exploiting the memristive character and the wiring of the junctions connecting the nanostructured network building blocks. Recently it is demonstrated that nanostructured Au films, fabricated by the assembling of gold clusters produced in the gas phase, have non‐linear and non‐local electric conduction properties caused by the extremely high density of grain boundaries and the resulting complex arrangement of nanojunctions. These observations suggest that nanostructured metallic films can be explored and exploited as a novel class of neuromorphic systems for unconventional electronic devices. Here it is reported that nanostructured cluster‐assembled Pt films show resistive switching activity, negative differential resistance, and reversible memory effects. These properties allow the use of nanostructured Pt films in programmable analog circuits, such as gain amplifiers and relaxation oscillators with fast response.